MAKNA SIMBOLIS TEH DAUN CENGKIH PADA MASYARAKAT KAWANGKOAN DI KABUPATEN MINAHASA - Donny Chandra Joshua Langi; Selvie Rumampuk; Titiek Mulianti (Universitas Sam Ratulangi, 2021)
In order to fulfill the needs of human life has been increasingly complex to develop culture and find tools that can be use in facilitating and enjoying as a form of adaptation to the environment in which they live. The ability to find and create everything is called the system of thought or human culture, so in this case culture is the whole knowledge that man has as a social being whose contents are tools of knowledge model that can be selectively used to understand and interpret the environmental actions faced and to encourage creating the actions that he needs , this is obtained by man from the process of learning and made himself like other individuals in his social group.Tea culture is one form of culture that exists in every region in the archipelago. The habit of drinking tea in Indonesia also does not know a special time, although most of us consume it in the morning, but it can actually be enjoy at any time. Clove leaf tea is a typical traditional beverage processed and has many benefits because it is different from tea drinks in general. For the community clove leaf tea drink has many benefits for health such as being able to provide warmth for the body, avoiding diseases, especially for women eliminate unpleasant odors and odors during childbirth. This clove leaf tea drink unconsciously became a knowledge system that formed local wisdom in Kawangkoan community.Â Keywords: drink, clove leaf tea, symbol